The Development of Science Note Learning Media for Alternative Energy Sources Theme in Islamic Elementary School - Riska Murtisari; Khusna Widhyahrini; Jaffar Abbas (Program Studi PGMI UIN Salatiga, 2022)
This research aims to develop Science Note, a learning media for alternative energy source themes, for Islamic elementary school students. The product was developed following the ADDIE model, consisting of the following stages: 1) preliminary study, 2) development of Science Note media, and 3). product effectiveness test. The data were analyzed qualitatively and quantitatively. In this study, the product was developed through several stages: (a) searching for real condition data and conducting needs analysis, (b) designing the Science Note, (c) Validating the product by involving media and material experts, and teachers, (d) Revising the product based on validators’ feedbacks. The subject of this research was the 4th grade of MI Ma’arif and MI Noborejo. Validation showed that Science Note media had a score of 3.77 (very good), and by the individual trial test with a score of 3.62. The effectiveness of science note media was tested using the t-test and it was obtained a tailed sig (2) of 0.000. p = 0.00 0.05. These results indicate that the Canva Science Note media is effective in the learning achievement of class VI Madrasah Ibtidaiyah students.